PENGEMBANGAN BUDAYA DAN IKLIM SEKOLAH - ASTUTI Astuti (Adaara: Jurnal Manajemen Pendidikan Islam, 2018)
Abstrct: This paper discusses the development of school culture and climate. Conducive school climate and culture is characterized by the creation of a safe, comfortable, and orderly learning environment so that learning can take place effectively. Conducive school climate and culture are so important that learners feel happy and positive about their schools, so that teachers feel valued, and that parents and communities feel welcome and engage. This can happen through the creation of positive norms and habits, harmonious relationships and cooperation based on mutual respect. The school climate can basically be put forward as an organizational climate that occurs in a school. School climate is the result of interaction media in school organizations. Keywords: Cultural development and school climate.